Constitutive modelling of the strain hardening behaviour of metastable AISI 301LN austenitic stainless steel as a function of strain and temperature - Mostert, R.J. (Roelf) (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2020.